The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/rbz4820190056
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic embryonic development of Guinea fowl compared to other domestic bird species

Abstract: Reproduction Full-length research article Macroscopic embryonic development of Guinea fowl compared to other domestic bird species ABSTRACT-Since few studies have addressed the embryonic development of Guinea fowl (Numida meleagris), the objective of the present study was to evaluate its embryonic development in the Cerrado region of Brazil and compare the results to published descriptions of the embryonic development of other domestic bird species. The commercialized weight for Guinea fowl eggs used in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The low level of production and consumption of guinea fowl meat in many countries is caused by the lack of tradition of eating this meat and the limited knowledge of consumers about its nutritional and health properties. Meat-oriented production of guinea fowl occurs in Africa, Asia, and Latin America in a free-range system ( Araújo et al, 2019 ). In the intensive production system, it is a viable activity in countries such as the United States and Canada, as well as France and Italy ( López-Pedrouso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low level of production and consumption of guinea fowl meat in many countries is caused by the lack of tradition of eating this meat and the limited knowledge of consumers about its nutritional and health properties. Meat-oriented production of guinea fowl occurs in Africa, Asia, and Latin America in a free-range system ( Araújo et al, 2019 ). In the intensive production system, it is a viable activity in countries such as the United States and Canada, as well as France and Italy ( López-Pedrouso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors emphasize that the products obtained from guinea fowl, including meat, have not yet been fully described, because they are mostly kept in extensive systems. Hence, the slower genetic improvement of this species results ( Abdul-Rahman et al, 2019 ; Araújo et al, 2019 ; López-Pedrouso et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a comprehensive investigation has been conducted on the development patterns of embryonic intestines of chicks, ducks, turkeys, guinea fowls, and pigeons ( Dong et al, 2012a , b ; Wilson et al, 2018 ; Araújo et al, 2019 ; Li et al, 2019 ; Givisiez et al, 2020 ). Dong et al (2012a) observed the expression of intestinal nutrient transporters increased with age, moreover, they noted that the expression of sugar transporter genes in pigeon jejunum was higher than that in other intestinal segments.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, for example, interest in Guinea fowl as an alternative to produce meat has been increasing. In fact, in such country, numidiculture has proven to be a profitable activity (Nahashon et al, 2006a), due to the nutritional value and yield of the guinea fowl carcass, reported by various authors (Mareko et al, 2006;Kokoszynski et al, 2011;Bernacki et al, 2012;Hoffman and Tlhong, 2012;Camas-Robles et al, 2020), standing out for its delicacy and flavor, compared to chicken, turkey, and duck meat (Araújo et al, 2019). Likewise, Guinea fowl eggs are gaining relevance in the US market as an alternative for the production of eggs for dishes (Nahashon et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%